More evidence from over 1.1 million subjects that the critical period for syntax closes in late adolescence - Chen, Tony; Hartshorne, Joshua K. (Cognition, 2021)
The ability to attain native-like proficiency of a second language is heavily dependent on the age at which learning begins. However, the exact properties of this phenomenon remain unclear, and the literature is divided. Recently, Hartshorne, Tenenbaum, & Pinker presented a novel computational analysis of over 600,000 subjects, estimating that the ability to learn syntax drops at 17.4 years of age [Hartshorne, J. K., Tenenbaum, J. B., & Pinker, S. (2018). A critical period for second language acquisition: Evidence from 2/3 million English speakers. Cognition, 177, 263–277]. However, the novelty of the dataset and analyses raises questions and suggests caution [Frank, M. C. (2018). With great data comes great (theoretical) opportunity. Trends in cognitive sciences, 22(8), 669–671]. In the present paper, we address several such concerns by employing improved psychometric measurement, calculating confidence intervals, and considering alternative models. We also present data from an additional 466,607 subjects. The results support the prior report of a sharp decline in the ability to learn syntax, commencing at the tail end of adolescence.